Addressing coloniality of power to improve HIV care in South Africa and other LMIC - Ordóñez, Claudia E.; Marconi, Vincent C.; Manderson, Lenore (Frontiers in Reproductive Health, 2023)
After more than forty years of multilateral international efforts to improve the health of all people around the world, substantial health inequalities persist among marginalized communities everywhere, most extensively in low- and middle-income countries (LMICs). In South Africa, the HIV epidemic began in the 1980s and its ending has become as elusive as achieving universal health care. Despite impressive achievements such as South Africa’s antiretroviral treatment program, the largest in the world, disadvantaged South Africans continue to experience disproportionate rates of HIV transmission. We describe the effectiveness of community-based primary health care and stakeholder engagement for HIV care improvement in South Africa. Our conclusion is that innovation in global public health must overcome the coloniality of power in LMICs effected through the imposition of development and health care models conceived in high-income countries (HICs). We advocate for a paradigm shift in global health structures and financing to effectively respond to the HIV pandemic in LMICs and propose ethically responsive, community-based stakeholder engagement as a key strategy to improve HIV care. We join in solidarity with community-based and local stakeholders’ efforts and call upon others to change the current status quo characterized by global public health power concentrated in HICs.